Heimdallr's Charm - Tolley Clive (Suomalainen Tiedeakatemia, 2023)
Having sketched a proposed interpretation of some of the god Heimdallr’s main
characteristics and associations, it is possible to consider what a charm devoted
to him may have been concerned with. After looking at what may be meant
by ‘charm metre’ (galdralag), I survey some poetic mentions of charms, and
bring in comparisons from other Germanic traditions (Old High German and
Old English), alongside some more recent Scandinavian charms. I then move
on to a neighbouring tradition, the more recent yet archaic Karelian charms,
particularly those relating to birth and creation. We cannot determine what
Heimdallargaldr may have encompassed, in terms either of its mythological
or incantatory content, but these parallel traditions suggest something of the
parameters within which it may have functioned.
Folklore and Old Norse Mythology